Quality of Life in GERD and Barrett’s Esophagus is Related to Gender and Manifestation of Disease - Lippmann, Quinn K. (2009)
INTRODUCTION: Gastroesophageal reflux disease (GERD) is a common condition that impacts patients’ health-related quality of life (HRQoL). The HRQoL of Barrett’s esophagus (BE) has been less well studied. Furthermore, it is unknown to what extent BE patients suffer from psychological distress as a result of carrying a diagnosis of a premalignant condition. We sought to compare BE and GERD (stratified by erosive (ERD) and non-erosive reflux disease (NERD)) with regards to HRQoL and psychological impact. METHODS: In this single-center study of subjects presenting for elective upper endoscopy, consecutive patients with BE and GERD were enrolled. Participants completed questionnaires assessing generic HRQoL (Medical Outcomes Study Short Form-36: SF-36), disease-specific HRQoL (Gastrointestinal Quality of Life Index: GIQLI), a measure of psychological distress (the Revised Hopkins Symptom Checklist: SCL-90R) and a patient-centered assessment of impact of disease severity (the GERD health-related quality of life measure: GERD HRQL). RESULTS: Patients with BE had the lowest symptom severity compared to those with NERD or ERD (GERD HRQL: 13.7 vs. 18 and 15.9 respectively, p<0.01). Those with BE also had better disease-specific quality of life compared to NERD or ERD patients (GIQLI: 137.2 vs. 124.3 and 131.0 respectively, p<0.001). After adjusting for potential confounding variables including symptom severity and gender, BE patients continued to demonstrate better disease-specific HRQoL, scoring 12.2 points higher on the GIQLI than NERD patients (95% CI 5.1 – 19.3) and 16.3 points higher than ERD patients (95% CI 5.4 – 27.3), as well as better generic HRQoL, scoring 4.8 points higher on the SF-36 physical component summary than NERD patients (95% CI 0.8 – 8.8) and 7.1 points higher than ERD patients (95% CI 1.2–13.1). There were no significant differences between groups in psychological distress, as demonstrated by the SCL-90R global severity index, though BE patients scored lower on the somatization domain compared to NERD and ERD patients. When stratified by gender, females with NERD and BE had worse disease-specific HRQoL than males. CONCLUSIONS: Patients with BE have better generic and disease-specific HRQoL when compared to patients with NERD and ERD. This difference is only partially attributable to lower symptom severity amongst BE patients. Psychological distress did not differ significantly amongst groups. Female gender was associated with worsened HRQoL regardless of GERD disease manifestation. Though more precise instruments may aid in detecting any HRQoL decrements in BE patients due to perceived cancer risk or fear of developing or dying from cancer, we were unable to demonstrate an additional decrement in HRQoL due to cancer risk in subjects with BE.